Citra Bisnis Ritel Sebagai Faktor Penting Kepuasan Dan Dampaknya Terhadap Loyalitas Pelanggan Di Pasar Swalayan Carrefour Semarang (Proceeding Fakultas Ekonomi, 2014)
The purpose of this study to develop and test the effect of the image, price perception, and promotion influencing satisfaction and its impact on customer loyalty in order to win the competition supermarkets in Semarang. The total sample of 112 respondents at Carrefour Supermarket Semarang. The sampling technique used in this study was purposive sampling. The results showed that image, price perception, and promotion. Thus, image, price perception, promotion, and customer satisfaction has a positive effect on customer loyalty. Mediating effect of customer satisfaction does not apply to the effect of image on customer loyalty , the effect of price perception on customer loyalty, and influence on customer loyalty promotion . Means that customer satisfaction does not mediate the effect of the image, the effect of price perception , and influence on customer loyalty promotion . This research incorporates Resources Based Theory. The limitation and implication for the future study and the managerial implication are also discussed in this study.Keywords: image, price perception, promotion, satisfaction, loyalty